2017
DOI: 10.1371/journal.pone.0167046
|View full text |Cite
|
Sign up to set email alerts
|

Traffic-related air pollution and spectacles use in schoolchildren

Abstract: PurposeTo investigate the association between exposure to traffic-related air pollution and use of spectacles (as a surrogate measure for myopia) in schoolchildren.MethodsWe analyzed the impact of exposure to NO2 and PM2.5 light absorbance at home (predicted by land-use regression models) and exposure to NO2 and black carbon (BC) at school (measured by monitoring campaigns) on the use of spectacles in a cohort of 2727 schoolchildren (7–10 years old) in Barcelona (2012–2015). We conducted cross-sectional analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Recent studies have shown that children living in urban areas with high population density and pollution are at higher risk of developing myopia. 1,42,43 Contrary to many cities in East Asia, the current sample was protected from these two factors because population density as well as pollution levels in Kalmar Län are low. 44 The pressure of education has also been linked to increased prevalence of myopia.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have shown that children living in urban areas with high population density and pollution are at higher risk of developing myopia. 1,42,43 Contrary to many cities in East Asia, the current sample was protected from these two factors because population density as well as pollution levels in Kalmar Län are low. 44 The pressure of education has also been linked to increased prevalence of myopia.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study had reported that myopia was associated with PM2.5 and NOx which could be an indicator of air pollution [ 29 ]. Exposure to air pollution had a weak link with development of myopia, and long-term studies should be implemented [ 30 ]. The outdoor light environment had been proved to play an important role in the onset and progression of myopia [ 31 ], but data concerning indoor light environment were limited.…”
Section: Discussionmentioning
confidence: 99%
“…Speculation about this factor has been fueled by the high levels of air pollution seem in some parts of China, but in fact, in international terms, Chinese cities rank well behind many cities in South Asia and the Middle East, where the prevalence of myopia is much lower than in Chinese cities (https://www.who.int/airpollution/ data/cities/en/, accessed Jan 30, 2019). Increased use of spectacles, presumably for myopia, has been associated with traffic-related pollution [154], but this may in fact be related to the association between urban residence and more myopia, as well as links to socioeconomic status, area of residence, and education [153].…”
Section: Pollutionmentioning
confidence: 99%